Roadside air quality and implications for control measures: A case study of Hong Kong. (July 2016) - Ai, Z.T.; Mak, C.M.; Lee, H.C.
Abstract: Traffic related air pollution is one of major environmental issues in densely populated urban areas including Hong Kong. A series of control measures has been implemented by Hong Kong government to cut traffic related air pollutants, including retrofitting the Euro II and Euro III buses with selective catalytic reduction (SCR) devices to lower nitrogen dioxide (NO2 ) emissions. In order to reveal the real-life roadside air quality and evaluate the effectiveness of the control measures, this study first analyzed the recent six-year data regarding concentrations of pollutants typically associated with traffic recorded in two governmental roadside monitoring stations and second conducted on-site measurements of concentration of pollutants at pedestrian level near five selected roads. Given that there is a possibility of ammonia leakage as a secondary pollutant from SCR devices, a special attention was paid to the measurements of ammonia level in bus stations and along roadsides. Important influencing factors, such as traffic intensity, street configuration and season, were analyzed. Control measures implemented by the government are effective to decrease the traffic emissions. In 2014, only NO2 cannot achieve the annual air quality objective of Hong Kong. However, it is important to find that particulate matters, rather than NO2, post potentially a short-term exposure risk to passengers and pedestrians. Based on the findings of this study, specific control measures are suggested, which are intended to further improve the roadside air quality. Highlights: Traffic induced roadside air pollution and control measures investigated. Six-year concentration data from roadside monitoring stations analyzed. Pedestrian-level concentration of pollutants along roadside measured. Nitrogen dioxide posts long-term exposure risk to roadside workers. Particulate matters post short-term exposure risk to roadside passengers.